School-Based Management in Efforts to Develop Student Life Skills in Community - Wahyudi, Apri; Mantik, Aliyah; Windayanti, Wiwin; Muhtarom, Muhtarom; Kusuma, Nurhadi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This study uses a qualitative approach. The technique of taking data sources in this study is using Snow Bolling Sampling. The data collection procedures used are observation, review, and documentation studies. In conducting this data analysis, the author uses several methods, namely the induction, deduction, and comparison methods. School-based management at SMP Islam Terpadu Insan Madani Boarding School strongly supports the effectiveness of efforts to develop students' life skills. This is done by integrating general life skills in each subject so that every teaching and learning activity aims to develop certain life skills. Second, organizing a